Sex Differences in Spontaneous Degranulation Activity of Intrahepatic Natural Killer Cells during Chronic Hepatitis B: Association with Estradiol Levels - Zuzana Macek Jilkova; Thomas Decaens; Alice Marlu; Hélène Marche; Evelyne Jouvin-Marche; Patrice N. Marche (Mediators of Inflammation)
Major sex differences are observed in the prevalence, intensity, and severity of hepatitis B virus (HBV) infection. Here, we investigated degranulation activity of circulating and intrahepatic natural killer (NK) cells from HBV and HCV chronically infected patients before any treatment (n=125). The frequency of CD107+ NK cells in the female liver was significantly higher compared to that in males during chronic HBV infection (p=0.002) and correlated with the plasma levels of estradiol (correlation coefficient r=0.634; p<0.0001). Our results clearly show sex differences in degranulation activity of intrahepatic NK cells of HBV-infected patients. This probably contributes to the ability of females to better deal with HBV disease.